Cholesterol Levels in Angiotensin Converting Enzyme Gene Polymorphisms in Schizophrenia Patients - Isra Thristy; Nanda Sari Nuralita; Debby Mirani Lubis (Universitas Muhammadiyah Sumatera Utara, 2023)
Abstract: Angiotensin-converting enzyme (ACE) is widely distributed on the surface of endothelial and epithelial cells. The renin-angiotensin system in the brain has implications for various functions, including cerebral blood circulation and brain protection, stress, depression, and the aetiology of schizophrenia. ACEs and angiotensin receptors can be found on dopaminergic neurons in the basal ganglia. Elevated levels of triglycerides and cholesterol can also be found in schizophrenic patients related to treatment and duration of the course of the disease. The purpose of this study was to determine the relationship between ACE gene polymorphism and cholesterol levels in schizophrenia patients. The design of this study was observational analytic with a cross-sectional approach. The sample in this study was schizophrenia patients who sought treatment at Madani Medan Hospital with a total of 42 people. The data obtained is then processed with the ANOVA one-way test. The results of the study were obtained from 42 samples, the most types of ACE gene polymorphisms were type II (76.2%), followed by the type of DD polymorphism (19%) and the least was the type of ID polymorphism (4.8%). The average value of cholesterol levels of the sample was 235.40 mg/dl with a standard deviation value of 47.618. Statistical test results of ACE gene polymorphism with cholesterol levels with p = 0.770 (p 0.05). It can be concluded that there is no relationship between the polymorphism of the ACE gene and the cholesterol levels of schizophrenic patients.